Determination of Trihalomethanes in Tap Water by UV-Vis Spectrophotometry - ARBAB ZAVAR, M.H.; ROUNAGHI, G.H.; CHAMSAZ, M.; ASHRAF, N. (Asian Journal of Chemistry, 2010)
A simple and sensitive spectrophotometric method based on Fujiwara reaction has been developed for determination of trihalomethanes in water. Determination of trihalomethanes was carried out by adsorption on Amberlite XAD-4 resin, elution with pyridine, addition of KOH to eluate and heating to measure the absorbance at 531 nm. Detection limit and linear range for the proposed method was 187 ng mL-1 and 0.2-8 μg mL-1, respectively. This rapid, sensitive, precise and low cost method enables water treatment facilities to respond quickly to investigate water quality.